Adsorption of Anionic Dyes from Aqueous Solution on Zeolite from Fly Ash-Iron Oxide Magnetic Nanocomposite (Journal of Atomic and Molecular Sciences, 2011)
Magnetic zeolite/iron oxide nanocomposite was prepared by mixing zeolite synthesized from coal fly ashes with magnetite nanoparticles in suspension and was used for the removal of Reactive Orange 16 (RO16) and Indigo Carmine (IC) from aqueous solutions. The effect of various experimental parameters such as contact time, pH, adsorbent dose and temperature were investigated. The experimental data were analyzed using the pseudo-first-order and pseudo-second-order adsorption kinetic models. The experimental data fit the second-order kinetic model. The Langmuir and Freundlich isotherm models were tested for their applicability. Results indicated that according to the Langmuir isotherm, the maximum sorption capacities are 1.1 and 0.58 $mg$$·$$g^{-1}$ for RO16 and IC, respectively. Thermodynamic parameters showed that adsorption of dyes were endothermic and spontaneous in nature.
Keywords: magnetically modified zeolite; coal fly ash; nanocomposite; adsorption; dye removal.